An Analysis of the Implementation of English for Specific Purposes (ESP) in Vocational High Schools: A Case Study of the Visual Communication Design Program at SMK Negeri 2 Gorontalo - Husain, Nurlaila (Jurnal Riksa Cendikia Nusantara, 2026)
This study aims to analyze the implementation of English for Specific Purposes (ESP) in English instruction within the Visual Communication Design (DKV) program at SMK Negeri 2 Gorontalo. The research employed a qualitative approach with a case study design to explore the extent to which classroom practices align with ESP principles, particularly in terms of needs analysis, materials development, and assessment. Data were collected through semi-structured interviews with one English teacher, classroom observations, and document analysis. The findings reveal that instruction has begun to reflect contextual ESP principles through the integration of digital design projects and vocabulary relevant to the students’ field of study. However, the implementation remains adaptive in nature and is not yet grounded in a systematic and formal needs analysis. Gaps were also identified in the reinforcement of technical vocabulary, pronunciation development, and performance-based assessment. The study underscores the importance of industry-oriented needs analysis and authentic evaluation strategies to strengthen ESP implementation in vocational education.